2020
DOI: 10.1101/2020.08.17.254912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Live-imaging of endothelial Erk activity reveals dynamic and sequential signalling events during regenerative angiogenesis

Abstract: The formation of new blood vessel networks occurs via angiogenesis during development, tissue repair and disease. Angiogenesis is regulated by intracellular endothelial signalling pathways, induced downstream of Vascular endothelial growth factors (VEGFs) and their receptors (VEGFRs). A major challenge in understanding angiogenesis is interpreting how signalling events occur dynamically within endothelial cell populations during sprouting, proliferation and migration. Erk is a central downstream effector of Ve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…To test this hypothesis, we first assessed the activation of the mitogen-activated protein kinase (MAPK)/extracellular regulated kinase (ERK) pathway, a downstream effector of both FGF and VEGF signaling, in CMs. To do so, we generated a transgenic line, Tg(myl7:ERK-KTR-Clover-P2A-H2B-mScarlet) , to monitor ERK activation through a kinase translocation reporter (de la Cova et al, 2017; Mayr et al, 2018; Okuda et al, 2020) (Fig. 4D).…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we first assessed the activation of the mitogen-activated protein kinase (MAPK)/extracellular regulated kinase (ERK) pathway, a downstream effector of both FGF and VEGF signaling, in CMs. To do so, we generated a transgenic line, Tg(myl7:ERK-KTR-Clover-P2A-H2B-mScarlet) , to monitor ERK activation through a kinase translocation reporter (de la Cova et al, 2017; Mayr et al, 2018; Okuda et al, 2020) (Fig. 4D).…”
Section: Resultsmentioning
confidence: 99%
“…In the future, it would be interesting to investigate the regenerative pathways activated by the cell‐death–induced calcium spike. Particularly, it has recently been shown that the extracellular signal‐regulated kinase (ERK) pathway is activated by calcium signaling in a regenerative model of vascular damage in zebrafish 47…”
Section: Discussionmentioning
confidence: 99%
“…Here we report the adaptation of the KTR technology for capturing ERK activity dynamics in Drosophila. Although initially developed for use in mammalian cell culture (Regot et al, 2014), ERK-KTR has since been successfully adapted in C. elegans , zebrafish and mouse and has enabled visualisation of ERK kinetics in a longitudinal manner (de la Cova et al, 2017; Mayr et al, 2018; Okuda et al, 2021; Pokrass et al, 2020; Simon et al, 2020). Combining the powerful advantages of Drosophila genetics with tissue-specific expression using the Gal4/UAS or Q systems means that Drosophila ERK-KTR is a versatile tool that will enable precise dissection of the dynamics of ERK signalling in a variety of physiological contexts.…”
Section: Discussionmentioning
confidence: 99%